Low‐dose immune tolerance induction in children with severe hemophilia A with high‐titer inhibitors: Type of factor 8 mutation and outcomes - Jie Sun; Zekun Li; Gang Li; Kun Huang; Di Ai; Guoqing Liu; Wanru Yao; Xingjuan Xie; Hao Gu; Yingzi Zhen; Zhenping Chen; Runhui Wu (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background No studies evaluated the role of F8 mutations in outcomes for low‐dose immune tolerance induction (ITI) in people with severe hemophilia A (SHA) with high‐titer inhibitors. Objectives To explore the association between F8 mutation types and low‐dose ITI outcomes in children with SHA with high‐titer inhibitors. Methods Children SHA with high‐titer inhibitors who received low‐dose ITI therapy at least for 1 year were included in this study. Based on the risk of inhibitor development, F8 mutations were classified into a high‐risk group and a non–high‐risk group. Rapid tolerance and the final ITI outcomes were assessed at the 12th and 24th month of treatment, respectively, and the predictor of outcomes was analyzed. Results Of 104 children included, 101 had F8 mutations identified. The children with non–high‐risk mutations presented a higher rate of rapid tolerance than those with high‐risk mutations (61.0% vs. 29.2%; p = 0.006). Among 72 children beyond 24 months of ITI, 55 children (76.4%) achieved success, 3 (4.2%) achieved partial success, and 14 (19.4%) failed. The children in the non–high‐risk group showed a higher success rate (86.8% vs. 43.8%; p = 0.001) and a shorter time to success (mean time, 9.3 months vs. 13.2 months; p = 0.04) compared to those in the high‐risk group. In multivariable logistic regression, F8 mutations were an independent predictor of ITI success (non–high‐risk group vs. high‐risk group, adjusted odds ratio [OR], 20.3; 95% confidence interval [CI], 3.5–117.8), as was the interval from inhibitor diagnosis to ITI start (adjusted OR, 0.95; 95% CI, 0.90–0.99). They remained the significant predictors when success time was taken into account in a Cox model. Conclusions Types of F8 mutation were a key predictor of outcomes for low‐dose ITI in children with SHA with high‐titer inhibitors. It can help to stratify the prognosis and guide clinical decisions.